Implementasi Bahasa Indonesia sebagai Mata Kuliah Umum dalam Pengembangan Kompetensi pada Mahasiswa Gizi - Diva Yolanda Misi; Annisa Azalia; Santaria Naibaho; Reza Nur Wahyuni; Muhammad Anggie Januarsyah Daulay (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study examines how the implementation of Bahasa Indonesia as a general course (MKU) has a strategic role in supporting the development of student competencies, especially in the field of nutrition science. This study uses a qualitative-descriptive method to investigate how effective the Bahasa Indonesia MKU is in improving academic communication skills, scientific literacy, and the delivery of information about nutrition science. The results of the study show that the Bahasa Indonesia MKU contributes greatly to the mastery of scientific writing skills, the creation of data-based nutrition reports, and the dissemination of persuasive information to the public. Students also showed improvements in critical and analytical thinking, which helped them make nutritional decisions. Therefore, the Bahasa Indonesia MKU functions as a course that is not only mandatory, but also as an important foundation for building the professionalism of nutrition students. This study emphasizes that the Bahasa Indonesia course must be integrated with the specific needs of the study program to produce graduates who are proficient and ready to contribute to society.